FAKTOR YANG MEMPENGARUHI PENDAPATAN PENGEMUDI OJEK ONLINE DI JABODETABEK - Ramadhan, Dwi Raihan; Wibisono, Yusuf (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.14.NO.02.TAHUN.2025DO - 10.24843/EEB.2025.v14.i02.p10, 2025)
Online ojek has a rapid development. The relationship between the driver and the service provider company is a partner. This partner status has an impact on rights and authorities that are different from workers. On the one hand, drivers have freedom and flexibility in working. On the other hand, they do not receive wages from the service provider company. Therefore, this study aims to see what factors affect the income of online ojek drivers. The research uses primary data obtained through questionnaires to online ojek drivers in Jabodetabek. In addition, this study uses multiple linear regression method using STATA application. The results found that age, status, expenses, distance and orders have a significant effect on the income of online ojek drivers in Jabodetabek. The results also found that the income of online ojek drivers varies widely and tends to be low. Researchers suggest that the parties pay more attention to the fate of online ojek drivers and make policies that benefit online ojek drivers, especially in terms of increasing the income of drivers such as providing bonuses, implementing fair tariffs and encouraging dynamic relationships between drivers and companies.